The Role Played by the Religious Leaders, Community Leaders/Elders and Other Stake Holders in Adoption of Alternative Rites of Passage in Oleguruone Sub-County, Nakuru County, Kenya - Chepkemoi, Rachel; parasitau, Damaris; O Ayiemba, Joshua (IJRDO - Journal of Social Science and Humanities Research, 2017)
This paper sought to examine the role played by religious leaders, teachers and village elders, in either supporting or discouraging ARP to replace FGM. Female Genital Mutilation (FGM) is practiced in many parts of the world although it is much prevalent in Africa. It is a cultural practice which has been going on for a long time, even though its origins all appear untraceable in human history. Despite this fact, FGM has been a key ritual event of initiation in various communities for girls since time immemorial. The practice of female genital mutilation/circumcision FGM/C dates back to ancient times. Female circumcision has existed for over 4,000-5,000 years originating in a period predating God’s covenant with Abraham to circumcise his people (male only).This act of circumcision gave the Israelites an identity and sense of belonging to the Jewish community which was God’s chosen Nation. It began in Egypt and was frequently performed by the ancient cultures of the Phoenicians, Hittites, and the ancient Egyptians. Those people had the idea that was based on the belief that, the foreskin was the feminine part of the male and the clitoris the masculine part of a woman. (Tanui 2006,) According to International Organization Interagency Statement Report (IOISR) (2008)